The Inhibition of Streptococcus mutans by He- Ne Laser via TBO Photosensitizer - Hassan, Layla M.; Jawad, Hussein A.; Salih, Dhuha S. (Iraqi Journal of Laser, 2006)
This work aims to investigate the inhibition of vitality of Streptococcus mutans, which is the causative agent of caries. A 632.8 nm He-Ne laser with the output power of 4.5mW was used in combination with toluidine blue O (TBO) at the concentration of 50μg/ml as a photosensitizer. Streptococcus mutans was isolated from 35 patients if carious teeth. Three isolates were chosen and exposed to different energy densities of He – Ne laser light 3.8, 11.7, 34.5 and 104.1 J/cm². After irradiation, substantial reduction was observed in the number of colony forming units (CFU)/ ml. The reduction in the number of CFU was increasing as the dose increased.